Penerapan Strategi Marketing Pada Aisyah Desert and Drinks Menggunakan Landing Page - Munawir, Munawir; Sri Sulistyawati, Upik (Divisi Riset, Lembaga Mitra Solusi Teknologi Informasi (L-MSTI), 2022)
The role of internet technology is felt to be increasingly important because it provides multiple benefits for digital marketing. landing page as an online shop system that is very accurate so that any information is included in it. Aisyah Desert and Drinks is one of the food and beverage businesses in Jembrana Regency. Due to the lack of media for offline promotion and information as well as to improve the quality of marketing. then a strategy was built by designing and entering online shop information that aims to make it easier for customers to order at Aisyah Desert and Drinks online based on a website in the form of a landing page. The advantage of using a landing page is being able to create informative and educational offering content, so that potential buyers are interested in buying products and will be very helpful in promoting businesses through this online system. in making this landing page using the waterfall method. This model is actually a